Iman dan Spiritualitas Membentuk Karakter Pemimpin Yang Beretika - Juliana Waruwu; Frenty Sariyati; Yan Pratama Tarigan; Arip. S. Sitompul; Ratna Saragih (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
As a very important figure, a good leader must have a good character and can be a role model for its members. Without a good leader, the institution being led cannot run well either. Good faith and spirituality produce ethical leadership and are able to become a superior and successful leader for anyone, be it in the family, society, government or other institutions. This study shows that faith and spirituality can shape the character of an ethical leader, while without good faith and spirituality, good ethics cannot be formed from a leader. Qualitative study is used accompanied by literature works. Data were collected through some writings ftrom books, articles, etc that discuss related topics. The results show that a leader needs good faith and spirituality not only to govern and provide direction to his subordinates but also to be an example and motivate his subordinates to also have good ethics